Board characteristics and financial decisions of indigenous Nigerian companies - Olumuyiwa , Olanrewaju Opeoluwa; Akinyede, Oyinlola Morounfoluwa (Corpus Intellectual, 2024)
The study investigates the relationship between board characteristics and financial decision within indigenous Nigerian companies, particularly the impacts of board characteristics on the investment, dividend and financial decision within indigenous Nigerian companies. Causal-comparative research design was used to investigate the effects of board characteristics and financial decision. Data was purposively gathered from 10 indigenous Nigerian companies listed on the Nigerian stock exchange between 2012 and 2021 having considered a population of 156 indigenous Nigerian companies quoted on Nigeria stock exchange (NGX) as at July 13 2023. The fixed effects model method of data analysis and Regression was employed.The findings revealed that larger board size positively impacted the Debt to Equity Ratio of the organization which is a financial decision. This aligns with resource dependence and agency theories as Debt to Equity Ratio is influenced by the presence of a Board Committee and greater Board Diligence. The findings also shows a positive relationship exists between Board size and the Dividend per share. Thus supporting the idea that larger boards enhance dividend decision-making and financial performance Board Committee and greater Board Diligence also had positive effects on Dividend per share. The findings further reveals a positive relationship between Board Size and Fixed asset ratio and between Board Committee and Fixed asset ratio and a negative relationship exists between Board Diligence and Fixed asset ratio thus indicating that Board characteristics have effect on the investing decision which affects the financial performance of Indigenous companies. These have practical implications for stakeholders in Nigeria’s financial and economic landscape, including policymakers, investors, and analysts. These financial and non-financial indicators are crucial for making informed investment decisions, implementing effective risk management strategies, and developing sound policy plans.